Immunodominance of poxviral-specific CTL in a human trial of recombinant-modified vaccinia Ankara. - Smith, C; Mirza, F; Pasquetto, V; Tscharke, D; Palmowski, M; Dunbar, P; Sette, A; Harris, A; Cerundolo, V (2005)
Many recombinant poxviral vaccines are currently in clinical trials for cancer and infectious diseases. However, these agents have failed to generate T cell responses specific for recombinant gene products at levels comparable with T cell responses associated with natural viral infections. The recent identification of vaccinia-encoded CTL epitopes, including a new epitope described in this study, allows the simultaneous comparison of CTL responses specific for poxviral and recombinant epitopes. We performed detailed kinetic analyses of CTL responses in HLA-A*0201 patients receiving repeated injections of recombinant modified vaccinia Ankara encoding a string of melanoma tumor Ag epitopes. The vaccine-driven CTL hierarchy was dominated by modified vaccinia Ankara epitope-specific responses, even in patients who had not received previous smallpox vaccination. The only recombinant epitope that was able to impact on the CTL hierarchy was the melan-A26-35 analog epitope, whereas responses specific for the weaker affinity epitope NY-ESO-1(157-165) failed to be expanded above the level detected in prevaccination samples. Our results demonstrate that immunodominant vaccinia-specific CTL responses limit the effectiveness of poxviruses in recombinant vaccination strategies and that more powerful priming strategies are required to overcome immunodominance of poxvirus-specific T cell responses.